2019
DOI: 10.1246/cl.190250
|View full text |Cite
|
Sign up to set email alerts
|

N-Fused Porphyrin: A Maverick Member of the Porphyrin Family

Abstract: as a Postdoctoral Fellow. In 1992, he started his independent academic carrier at Oita University as an Associate Professor. In 1997, he moved to Kyoto University as an Associate Professor and worked with Prof. Atsuhiro Osuka. In 2002, he was appointed as a Full Professor at Kyushu University. His current research focuses on the synthesis of porphyrin analogues, so-called N-confused porphyrinoids, and the development of NIR dyes with novel function. Motoki Toganoh received his Ph.D. in 2003 from the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The resulting sp 2 C16−O2 and C15−O1 bonds were typical double bonds with lengths of 1.244(5) and 1.270(5) Å, respectively. In contrast to the sitting atop metal coordination in the previously reported NFP complexes, Ir ‐ 3 displayed in‐plane coordination of the iridium cation to the NNOC core [20,38] . The corresponding σ‐carbon donor site, which originated from the cyclooctene ligand fused to the α‐confused pyrrole ring of NFP, led to the formation of an unusual C( sp 3 )‐Ir bond with a bond length of 2.069(4) Å (Figure S10).…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation
“…The resulting sp 2 C16−O2 and C15−O1 bonds were typical double bonds with lengths of 1.244(5) and 1.270(5) Å, respectively. In contrast to the sitting atop metal coordination in the previously reported NFP complexes, Ir ‐ 3 displayed in‐plane coordination of the iridium cation to the NNOC core [20,38] . The corresponding σ‐carbon donor site, which originated from the cyclooctene ligand fused to the α‐confused pyrrole ring of NFP, led to the formation of an unusual C( sp 3 )‐Ir bond with a bond length of 2.069(4) Å (Figure S10).…”
Section: Figurementioning
confidence: 85%
“…In this work, we investigated the degradation of N‐fused porphyrin (NFP; 1 ), an asymmetric porphyrin congener derived from 6 through an oxidative internal ring fusion with the adjacent pyrrole (Figure 1c) [20] . The inner fused [5.5.5]‐pentacyclic moiety in the fused analog 1 contributed to the distinct near‐infrared (NIR) optical properties, which were attributed to the distinct 18π aromatic structure [21,22] .…”
Section: Figurementioning
confidence: 99%
“…Then, we discuss model (iv). The pyrrole inversion of NCP is commonly observed in the synthesis of N-fused porphyrin from NCP. Theoretical study has shown that the activation energy of pyrrole ring rotation in 2a is 25.3 kcal/mol, which is much lower than that of TPP, which is 36.5 kcal/mol (Figure S10). , The inverted arrangement of the confused pyrrole ring has been reported for a NCP dimer, in which two NCP molecules are covalently linked at the inner carbon atoms, and a hydrogen bond is formed between the inner N4-H and N1 of the inverted confused ring .…”
Section: Resultsmentioning
confidence: 99%
“…N-Fusion in porphyrins and expanded porphyrins has created significant curiosity since their structures, and spectral and coordination properties are quite unique and different from their non-fused congeners. 1–6 Fusion occurs because of intra-molecular bond formation in the inner core of a porphyrinoid skeleton due to dehydrogenation or oxidation. 3 Porphyrinoids with a flexible macrocyclic framework generally show a tendency to undergo intramolecular oxidation to form fused moieties in their macrocyclic framework.…”
Section: Introductionmentioning
confidence: 99%
“…1–6 Fusion occurs because of intra-molecular bond formation in the inner core of a porphyrinoid skeleton due to dehydrogenation or oxidation. 3 Porphyrinoids with a flexible macrocyclic framework generally show a tendency to undergo intramolecular oxidation to form fused moieties in their macrocyclic framework. 7 Pyrrole/heterocyclic ring inversion is more common in expanded porphyrinoids with more than four pyrrole rings due to their intrinsic flexible nature leading to easier intramolecular fusion in the system such as N-fused pentaphyrin I (Chart 1).…”
Section: Introductionmentioning
confidence: 99%